Defining and operationalizing path dependency for the development and monitoring of adaptation pathways. (January 2022) - Hanger-Kopp, Susanne; Thaler, Thomas; Seebauer, Sebastian; Schinko, Thomas; Clar, Christoph
Highlights: Adaptation pathways approaches are useful to analyze and anticipate path dependencies. Systematic operationalization of path dependency for flood risk management planning. Seven specific entry points cover all aspects of path dependency in adaptation pathways approaches. We exemplify self-reinforcing mechanisms for flood risk management. Understanding past dependencies and lock-in could further improve pathways approaches. Abstract: Adaptation pathway approaches (APAs) have become an increasingly popular means of facilitating local and regional anticipatory planning under the influence of climate change. Many studies in this field of research identify path dependencies as a key barrier to adaptation efforts. However, their respective definitions of path dependency are often vague and impede a comprehensive integration of this concept into APAs. We fill this gap by systematically exploring the constituent characteristics and conditions of path dependency based on the original theoretical literature that emerged in the 1980s and early 2000s. We then propose an operationalization based on examples of flood risk management practice, and highlight ways in which APAs may contribute to revealing and anticipating technological and institutional path dependencies. This conceptual work serves as a comprehensive and systematic baseline for analyzing path dependency in empirical studies using APAs within and beyond the flood risk context.